Chronic pulmonary aspergillosis complicating sarcoidosis. Issue 6 (15th June 2017) - Uzunhan, Yurdagül; Nunes, Hilario; Jeny, Florence; Lacroix, Maxime; Brun, Sophie; Brillet, Pierre-Yves; Martinod, Emmanuel; Carette, Marie-France; Bouvry, Diane; Charlier, Caroline; Lanternier, Fanny; Planès, Carole; et al.
Chronic pulmonary aspergillosis (CPA) complicating sarcoidosis (SA) is associated with high mortality, and there is a lack of clarity regarding the relative contributions of SA or CPA. This was a retrospective single-centre study on CPA-SA. In total, 65 patients (44 men), aged 41.4±13.5 and 48.3±11.9 years at the time of SA and CPA diagnoses, respectively, were included between 1980 and 2015. Of these, 64 had fibrocystic SA, most often advanced, with composite physiological index (CPI) >40 (65% of patients) and pulmonary hypertension (PH) (31%), and 41 patients (63%) were treated for SA (corticosteroids or immunosuppressive drugs). Chronic cavitary pulmonary aspergillosis (CCPA) was the most frequent CPA pattern. Regarding treatment, 55 patients required long-term antifungals, 14 interventional radiology, 11 resection surgery and two transplantation. Nearly half of the patients (27; 41.5%) died (mean age 55.8 years); 73% of the patients achieved 5-year survival and 61% 10-year survival. Death most often resulted from advanced SA and rarely from haemoptysis. CPI, fibrosis extent and PH predicted survival. Comparison with paired healthy controls without CPA did not show any difference in survival, but a higher percentage of patients had high-risk mould exposure. CPA occurs in advanced pulmonary SA. CPA-SA is associated with high mortality due to the underlying advanced SA rather than to the CPA. CPI, fibrosis extent and PH best predict outcome. CPA occurs in advanced pulmonary sarcoidosis, and survival is predicted by CPI, PH and fibrosis extent http://ow.ly/R3w830b2HvR